Dimethylguanidino Valerate: A Lifestyle‐Related Metabolite Associated With Future Coronary Artery Disease and Cardiovascular Mortality. Issue 19 (1st October 2019) - Ottosson, Filip; Ericson, Ulrika; Almgren, Peter; Smith, Einar; Brunkwall, Louise; Hellstrand, Sophie; Nilsson, Peter M.; Orho‐Melander, Marju; Fernandez, Céline; Melander, Olle
Abstract : Background: Identification of lifestyle modifiable metabolic pathways related to cardiometabolic disease risk is essential for improvement of primary prevention in susceptible individuals. It was recently shown that plasma dimethylguanidino valerate (DMGV) levels are associated with incident type 2 diabetes mellitus. Our aims were to investigate whether plasma DMGV is related to risk of future coronary artery disease and with cardiovascular mortality and to replicate the association with type 2 diabetes mellitus and pinpoint candidate lifestyle interventions susceptible to modulate DMGV levels. Methods and Results: Plasma DMGV levels were measured using liquid chromatography‐mass spectrometry in a total of 5768 participants from the MDC (Malmö Diet and Cancer Study—Cardiovascular Cohort), MPP (Malmö Preventive Project), and MOS (Malmö Offspring Study). Dietary intake assessment was performed in the MOS. Baseline levels of DMGV associated with incident coronary artery disease in both the MDC (hazard ratio=1.29; CI=1.16–1.43; P <0.001) and MPP (odds ratio=1.25; CI=1.08–1.44; P =2.4e‐3). In the MDC, DMGV was associated with cardiovascular mortality and incident coronary artery disease, independently of traditional risk factors. Furthermore, the association between DMGV and incident type 2 diabetes mellitus was replicated in both the MDC (hazard ratio=1.83; CI=1.63–2.05; P <0.001) and MPP (odds ratio=1.65; CI=1.38–1.98; P <0.001). Intake of sugar‐sweetened beverages was associated with increased levels of DMGV, whereas intake of vegetables and level of physical activity was associated with lower DMGV. Conclusions: We discovered novel independent associations between plasma DMGV and incident coronary artery disease and cardiovascular mortality, while replicating the previously reported association with incident type 2 diabetes mellitus. Additionally, strong associations with sugar‐sweetened beverages, vegetable intake, and physical activity suggest the potential to modify DMGV levels using lifestyle interventions.